A thermo-economic based method for the design of process heat solar systems. (August 2020) - Franco, A; Bertola, G
Abstract: In this paper, the perspectives of production of thermal energy for industrial process heat from solar energy are considered. This represents a quite relevant topic for an overall containment of using fossil fuels with the objectives of reducing the impact of fossil fuel use. In particular, the paper outlines a thermo-economic design methodology taking into account the main variables problem (solar source, system architecture, design constraints, load type and distribution, design criteria and optimization criteria). The innovative element of the methodology is the consideration, among the various costs, of an economic penalty given to the operation of the auxiliary boiler. The results of the application in a particular case are shown in the final section of the paper, showing how it could be possible to increase the value of the solar share, up to 80% with respect to the conventional design method, that often limit this value at 60%.